Computer assisted sperm analysis - the relationship to bull field fertility, possible errors and their impact on outputs: A review - SIMONIK, O; SICHTAR, J; KREJCARKOVA, A; RAJMON, R; STADNIK, L; BERAN, J; DOLEZALOVA, M; BINIOVA, Z (The Indian Journal of Animal Sciences, 2015)
Sperm motility is one of the indicators most evaluated before and after cryopreservation, regarding quality and fertilizing ability. The present review provides complex information about the possible negative effects on the results of computer assisted sperm analysis (CASA) and also reflects a possible connection of these results to bull field fertility. Recently, there has been a growing interest in sperm motility assessment by CASA to determine sperm motion more accurately and objectively than by subjective evaluation. CASA systems have been routinely used in most research laboratories and also with increasing tendency in the case of insemination centres. However, objectivity and comparison of CASA results through laboratories can be impacted unfavourably. This is in particular due to the absence of standardization for bull sperm motility evaluation and the presence of drawbacks in the form of human and non-human factors. Investigators have recently turned to the possible association of CASA results with the prediction of bull field fertility. However, the studies suffer from discrepancies, thus a clear relationship has not yet been confirmed. Specific combinations of motility parameters with accurate determination of sperm subpopulations could represent another part in the complex system of providing the ability to predict fertility in vivo. The task of future works should be to establish standardization regarding sperm motility evaluation of specific animals, in addition to the settings and algorithms of CASA systems. Furthermore, predictive value CASA outputs to bull field fertility demand more extensive research aimed at a more precise definition of this relationship.